Managing Change - Dibsono, Dibsono (Forum Manajemen; Vol 12 No 67 (1998): Forum Manajemen Prasetiya Mulya | Desember 1998- Januari 1999, 1998)
Todays winning companies are those that are able to successfully adapt and capitalize on rapidly changing - unpredictable environments. The ability to manage change has become one of the key success factors of every organization to survive and grow. In some cases, organizations have no choice but to make the fundamental changes (Kilman & Covin, 1998) otherwise they were not ever survive. Successful change depends on the right decision on content, scale and direction and, the level of acceptance of the organization's people over the idea of change.